Virulence characteristics of a new race of the parasitic angiosperm, Sriga gesnerioides, from southern Benin on cowpea (Vigna unguiculata) - Lane, J.A.; Moore, T.H.; Cardwell, K.; Singh, B.; Bailey, M. (1994)
An in vitro growth system was used to determine the virulence of two samples of Striga gesnerioides from Zakpota in southern Benin. Cowpea variety B301, previously considered resistant to all races of S. gesnerioides, was susceptible to both samples of the parasite. Two other cowpea varieties, 58–57 and IT81D-994, were totally resistant. Resistance in 58–57 was associated with a hypersensitive necrosis of infected roots, whilst IT81D-994 supported production of small S. gesnerioides tubercles with stems which failed to develop. Striga gesnerioides from southern Benin is the fourth race of the parasite to be identified, and the first with virulence on variety B301. The implications for breeding cowpeas with resistance to S. gesnerioides are discussed.